Intraoral stereoradiography visualization with virtual reality: peri-implant bone level estimation accuracy – An in vitro study - Jorge Ferreira da Costa; João Caramês; Daniel Hachmeister (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial, 2025)
Objectives: The main objectives of this in vitro study were to evaluate the accuracy and precision of stereoradiography with virtual reality in measuring peri-implant bone level compared to conventional 2D radiography, and to find which stereoscopic angles between images lead to higher accuracy and precision. Another objective was to develop a virtual reality method for viewing pairs of stereoscopic radiographs, to archive, to present, and analyze the acquired stereoscopic images. Methods: A blinded laboratory study compared 40 samples of randomly positioned implants in 10 artificial bone blocks simulating random bone defects and crestal angulations. 320 pairs of different stereoscopic angulation images were analyzed using a head-mounted display system. A total of 1280 measurements of the mesial, distal, buccal, and lingual margins were made, in a randomized order, using 0.4 mm cylindrical threads as reference, giving a 0.2 mm maximum precision in measurements. Results: The median absolute error and relative error interquartile range were lower in stereoscopic images. The observers’ error of bone height estimation reduced substantially when stereoscopic images were used, even at low angular disparities such as 2° of stereopsis. Observers reported viewing discomfort at angles above 6º. Conclusions: Stereoradiography significantly reduced the error in bone height estimation, with any stereoscopic angle, compared to 2D. Augmented/virtual reality technology empowers stereoradiography, offering a more affordable and user-friendly imaging system.